2018
DOI: 10.4236/jssm.2018.114030
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Team-Member Exchange and Prospects

Abstract: Team-member exchange refers to individual's perception of the quality of working relationships as the whole within the team, which has been recognized by many scholars to the importance of team processes. However, the research of team-member exchange is still scarce. To advance team-member exchange of research, and gradually build and improve the development of team-member exchange theory paralleled with leader-member exchange theory, this paper reviews recent team-member exchange research in aspects of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 71 publications
2
25
1
3
Order By: Relevance
“…The concept of TMX and new groups in the workplace is not much different, they are both focused on what work must be done so that organizational goals are achieved (Chen, 2018). Rich et al (2010), recognizes work engagement as a role-based motivation concept that captures how a person expresses himself in work roles by investing his physical, emotional, and cognitive energy together.…”
Section: Organizational Socialization Tactics and Job Engagementmentioning
confidence: 99%
“…The concept of TMX and new groups in the workplace is not much different, they are both focused on what work must be done so that organizational goals are achieved (Chen, 2018). Rich et al (2010), recognizes work engagement as a role-based motivation concept that captures how a person expresses himself in work roles by investing his physical, emotional, and cognitive energy together.…”
Section: Organizational Socialization Tactics and Job Engagementmentioning
confidence: 99%
“…Horizontal relationships complement vertical relationships in facilitating proactive performance. Coworkers may offer socio-emotional and informational resources that are useful to proactive behaviors [ 20 , 55 , 56 ]. Indeed, Vough et al [ 21 ] noted that individuals interact with and rely on others in many ways to accomplish their proactive goals, suggesting that interpersonal interactions may facilitate proactive performance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the effectiveness of work interactions, communication and coordination with team members 1 as well as assistance provided by a team member through the introduction of enhanced work methods, 57 as referred to TMX, were critical for workplace innovation. 58 These dimensions are influenced by AMO-HR practices. 41 More importantly, the effectiveness of member-team relationship engenders employee proactivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, HR practices like work design flexibility significantly affected team outcomes such as team effectiveness, performance and innovation. 58 In a study on high-performance HR practices and team creativity, Ma et al 41 indicated that there is a significant effect of AMO-HR practices on team creativity through team efficacy and knowledge sharing. On the other hand, researchers mentioned several positives of the relationship between the employee and the team members—the most important of these positives are improving employee performance and proactive employee behavior.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%